The SIRT1/Nrf2 signaling pathway mediates the anti-pulmonary fibrosis effect of liquiritigenin - Qingzhong Hua; Lu Ren (BMC, 2024)
Abstract Background At present, the treatment options available for idiopathic pulmonary fibrosis are both limited and often come with severe side effects, emphasizing the pressing requirement for innovative therapeutic alternatives. Myofibroblasts, which hold a central role in pulmonary fibrosis, have a close association with the Smad signaling pathway induced by transforming growth factor-β1 (TGF-β1) and the transformation of myofibroblasts driven by oxidative stress. Liquiritigenin, an active compound extracted from the traditional Chinese herb licorice, boasts a wide array of biomedical properties, such as anti-fibrosis and anti-oxidation. The primary objective of this study was to examine the impact of liquiritigenin on bleomycin-induced pulmonary fibrosis in mice and the underlying mechanisms. Methods The anti-pulmonary fibrosis and anti-oxidant effects of liquiritigenin in vivo were tested by HE staining, Masson staining, DHE staining and bio-chemical methods. In vitro, primary mouse lung fibroblasts were treated with TGF-β1 with or without liquiritigenin, the effects of liquiritigenin in inhibiting differentiation of myofibroblasts and facilitating the translocation of Nrf2 were valued using Quantitative real-time polymerase chain reaction (Q-PCR), western blotting and immunofluorescence. Nrf2 siRNA and SIRT1 siRNA were used to investigate the mechanism underlies liquiritigenin's effect in inhibiting myofibroblast differentiation. Results Liquiritigenin displayed a dose-dependent reduction effect in bleomycin-induced fibrosis. In laboratory experiments, it was evident that liquiritigenin possessed the ability to enhance and activate sirtuin1 (SIRT1), thereby facilitating the nuclear translocation of Nrf2 and mitigating the oxidative stress-induced differentiation of primary mouse myofibroblasts. Moreover, our investigation unveiled that SIRT1 not only regulated myofibroblast differentiation via Nrf2-mediated antioxidant responses against oxidative stress but also revealed liquiritigenin's activation of SIRT1, enabling direct binding to Smad. This led to decreased phosphorylation of the Smad complex, constrained nuclear translocation, and suppressed acetylation of the Smad complex, ultimately curtailing the transcription of fibrotic factors. Validation in live subjects provided substantial evidence for the anti-fibrotic efficacy of liquiritigenin through the SIRT1/Nrf2 signaling pathway. Conclusions Our findings imply that targeting myofibroblast differentiation via the SIRT1/Nrf2 signaling pathway may constitute a pivotal strategy for liquiritigenin-based therapy against pulmonary fibrosis.